The design optimization of nanostructured hierarchical electrodes for solid oxide cells by artificial impregnation - Davide Cademartori; Maxime Hubert; Peter Cloetens; M. Paola Carpanese; Jérôme Laurencin (Materials & Design, 2024)
Microstructural correlations of impregnated freeze tape cast scaffolds for solid oxide cells are studied by coupling experimental and modelling approaches. The functional and supporting layers of the hierarchical porous backbones are initially reconstructed by synchrotron X-ray micro- and nano-holotomography, respectively. A particle-based model was then built to numerically infiltrate the scaffold walls with hemispherical nanoparticles. The electrode microstructural properties are evaluated on the artificially impregnated electrodes as function of the catalyst loading. A parametric investigation on the effect of the nanoparticle size is performed to analyse the evolution of the electrode characteristics. It has been shown that the volume fraction of the infiltrated phase necessary to reach the percolating threshold is increased while increasing the nanoparticle size. The density of active sites presents a maximum as function of the catalyst loading that depends on the particle size. The volume fraction of infiltrated phase required to reach the percolating threshold in the diffusion layer is one order of magnitude lower than in the functional layer (∼1 vol% compared to 3–8 vol%, respectively). The analyses contained in this paper aim at guiding the manufacturing process to the shaping of innovative electrodes microstructures combining both high activation and mass transfer properties.